Application of The Autoregressive Integrated Moving Average (ARIMA) Box-Jenkins Method in Forecasting Inflation Rate in Aceh - Syahrini, Intan; Radhiah, Radhiah; Damanik, Wirda Fadhila (Syiah Kuala University, 2023)
Inflation is an increase in the price of goods and services, in general that occurs continuously over a certain period. The government in a country or region needs to examine and pay attention to inflation data in the past to find out the inflation rate movement in a region. This study aims to predict the inflation rate in Aceh Province in the period September 2021 to January 2022 using the Box-Jenkins Autoregressive Integrated Moving Average (ARIMA) method. The best model obtained in this study is the ARIMA(2,0,2) model, which has a reasonably good forecasting accuracy value. The accuracy measured using the RMSE (Root of Mean Square) and MAE (Mean Absolute Error) values are close to zero, namely 0.474 and 0.373, respectively. The forecast results from inflation value this period classified into the category of mild inflation, where the increase in the price of goods that occurred during that period was still below 10%, so it did not impact the regional economy.